Clinical Outcomes of Permanent Left Bundle Branch Area Pacing in Patients With Left Bundle Branch Block and Left Ventricular Ejection Fraction >35 vs. ≤35% - Jiang, Zhixin; Wu, Tian; Wu, Yixian; Chen, Zenghong; Yang, Wen; Chen, Chongchong; Zhou, Xiujuan; Shan, Qijun (Frontiers in Cardiovascular Medicine, 2022)
Aims. The present study aimed to compare the effects of left bundle branch area pacing (LBBAP) on cardiac function and clinical outcomes in patients with left bundle branch block (LBBB) and left ventricular ejection fraction (LVEF) > 35% versus ≤ 35%. Methods and Results. 36 consecutive patients with LBBB and LVEF < 50% were enrolled. All patients were followed up for a mean of 6 months. The successful LBBAP was defined as a paced QRS complex presented as right bundle branch block (RBBB) morphology and QRSd < 130ms. Echocardiography parameters, pacing parameters and clinical outcomes were collected. The successful LBBAP was achieved in 77.8% of all cases (28/36). In LVEF > 35% group (70±8 years, 9 male), the success rate was 81.0%(17/21). QRSd significantly decreased from 174±23ms to 108±13ms (P<0.001). The pacing threshold and R-wave amplitude were 0.6±0.2V @ 0.5ms and 12±7mV, respectively. In LVEF ≤ 35% group (69±5 years, 9 male), the success rate was 73.3%(11/15) with QRSd decreasing from 188±25ms to 107±11ms (P<0.001). The hyperresponders to LBBAP (functional recovery and LVEF ≥ 50%) in LVEF > 35% group was 52.9% , which were almost twice of that in LVEF ≤ 35% group (33.3%). Whether patients had LBBAP or left ventricular septal pacing (LVSP), patients in the LVEF > 35% group showed significantly lower incidence of heart failure hospitalizations or death from any cause (hazard ratio in LVEF > 35% group, 0.22; 95%CI, 0.06 to 0.75, P = 0.011). Conclusions. LBBAP can significantly shorten the QRSd and improve cardiac function in LBBB patients with either LVEF > 35% or ≤ 35%. LBBAP should be considered as an effective therapy for preventing the deterioration of cardiac function in early-stage heart failure patients with LBBB and LVEF > 35%.